Kismet hacking - Haines, Brad.; Schearer, Michael J.; Thornton, Frank (Thorn) (Burlington, MA : Syngress Pub., 2008)
Kismet is the industry standard for examining wireless network traffic, and is used by over 250,000 security professionals, wireless networking enthusiasts, and WarDriving hobbyists. Unlike other wireless networking books that have been published in recent years that geared towards Windows users, Kismet Hacking is geared to those individuals that use the Linux operating system. People who use Linux and want to use wireless tools need to use Kismet. Now with the introduction of Kismet NewCore, they have a book that will answer all their questions about using this great tool. This book continues in the successful vein of books for wireless users such as WarDriving: Drive, Detect Defend. *Wardrive Running Kismet from the BackTrack Live CD *Build and Integrate Drones with your Kismet Server *Map Your Data with GPSMap, KisMap, WiGLE and GpsDrive.
Includes index.
Keywords: Wireless communication systems -- Security measures; Computer networks -- Security measures; Kismet (Electronic resource); Electronic books